PENGARUH STRES KERJA, KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION MEDICAL REPRESENTATIVE - Muhammad Irfan Nasution (Universitas Mercu Buana, 2017)
Abstract. This study porpose to examine the effect of job stress on job satisfaction, jobstress on organizational commitment, Job Satisfaction to organizational commitment,stress work to move intention, job satisfaction to move intention, organizationalcommitment to move intention, indirect influence between work stress Organizationalcommitment to job satisfaction, job stress on. The sample in this research is 40 medicalrepresentatives of PT. Pharmaceutical Industry Gracia Pharmindo Branch of NorthSumatra, Technique of completion of this research data using the interview, andquestionnaire. Data analysis technique used is Path Analysis. The results of this studyindicate job stress and negativity to the significance of job satisfaction and commitmentto organizational commitment, significant and significant work stress on shiftingintentions, job satisfaction and commitment to shifting intentions, positive andsignificant hard work towards turnover intention commitment through job satisfaction,stress significant and significant work on turnover intention through commitment oforganization Keywords: Job Stress, Job Satisfaction, Organizational Commitment, TurnoverIntention